2016
DOI: 10.1038/ncomms13401
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative insult can induce malaria-protective trait of sickle and fetal erythrocytes

Abstract: Plasmodium falciparum infections can cause severe malaria, but not every infected person develops life-threatening complications. In particular, carriers of the structural haemoglobinopathies S and C and infants are protected from severe disease. Protection is associated with impaired parasite-induced host actin reorganization, required for vesicular trafficking of parasite-encoded adhesins, and reduced cytoadherence of parasitized erythrocytes in the microvasculature. Here we show that aberrant host actin rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
62
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 74 publications
4
62
0
Order By: Relevance
“…Some studies have observed that parasites can grow normally in AS RBCs at 3% and 5% O 2 (19,(38)(39)(40). This may be due to technical differences in culture format and growth assessments.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have observed that parasites can grow normally in AS RBCs at 3% and 5% O 2 (19,(38)(39)(40). This may be due to technical differences in culture format and growth assessments.…”
Section: Discussionmentioning
confidence: 99%
“…These two hemoglobin variants have been associated with protection against severe malaria syndromes in numerous epidemiological studies 4 , and mechanistic hypotheses proposed to explain this protection include impaired blood stage parasite development 5 7 , reduced cytoadherence of infected red blood cells 8 , 9 , which is linked to the redox imbalance of hemoglobinopathies and its effects on the export of parasite-encoded proteins 10 , 11 , tolerance to malaria infection related to heme catabolism by heme oxygenase-1 12 , or accelerated acquisition of immunity 13 15 . Life-threatening episodes, however, represent only a small proportion of falciparum infections 16 , including in susceptible individuals 1 , and these same mechanisms might regulate other epidemiologically important parameters in non-severe infections, such as duration of parasite carriage and infectiousness.…”
Section: Introductionmentioning
confidence: 99%
“…In support of this latter hypothesis, two recently-published studies have shown that in static adhesion assays, VAR2CSA-expressing FCR3 parasites in HbAS and HbAC erythrocytes exhibit significant reductions in adherence to CSA compared to those grown in HbAA erythrocytes, this decreased binding being much greater for parasitized HbAC than HbAS erythrocytes 26, 27 . However, these studies assessed only a single parasite strain in static but not flow adhesion assays.…”
Section: Discussionmentioning
confidence: 76%